2019
DOI: 10.3390/nu11061419
|View full text |Cite
|
Sign up to set email alerts
|

Pathways from Food Insecurity to Health Outcomes among California University Students

Abstract: The prevalence of food insecurity (FI) among college students is alarmingly high, yet the impact on student health has not been well investigated. The aim of the current study was to examine the simultaneous relationships between food insecurity and health-related outcomes including body mass index (BMI) and overall health in a college student population. Randomly sampled students in the University of California 10 campus system were invited to participate in an online survey in spring 2015. The analytic sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
79
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 28 publications
5
79
1
1
Order By: Relevance
“…Lastly, the relatively small sample size of this study may not have been adequate to capture all potential differences between food-secure and food-insecure students. For example, food insecurity was not associated with BMI or body fat percentage in this study, though many previous studies have found food insecurity to be associated with obesity [24,37,[40][41][42].…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Lastly, the relatively small sample size of this study may not have been adequate to capture all potential differences between food-secure and food-insecure students. For example, food insecurity was not associated with BMI or body fat percentage in this study, though many previous studies have found food insecurity to be associated with obesity [24,37,[40][41][42].…”
Section: Discussioncontrasting
confidence: 91%
“…In a study of university students from New Jersey, food insecurity increased the odds of a student being in the lower 10% for GPA and decreased the odds of a student being in the upper 10% for GPA [23]. In college students from California, food insecurity has been associated with poor health behaviors such as limited physical activity, consuming fewer servings of fruits and vegetables, and not getting enough sleep [24]. In another study that looked at college students from Florida, Maine, Tennessee, Alabama, South Dakota, Kansas, New York, and West Virginia, food-insecure students had poorer sleep, higher stress, and a higher odds of disordered eating behaviors compared to food-secure students [25].…”
Section: Introductionmentioning
confidence: 99%
“…through symptoms of fatigue due to reduced dietary quality and potential deficiencies or limited financial possibilities to engage in sports). In turn, a decrease in physical activity could increase obesity prevalence through an altered energy expenditure [30]. Further, living situation and stressors (which might trigger unhealthy coping mechanisms like smoking) were previously indicated as potential mediators in this relationship [13,31].…”
Section: Potential Mediating Variables and Covariatesmentioning
confidence: 97%
“…To evaluate the magnitude of disparity in obesity due to food insecurity that would remain if an intermediate or downstream determinant is changed, we selected various potential mediating variables on the basis of the literature [13,30,31]. The association between food insecurity and weight was previously found to be mediated by lifestyle health behaviors like diet quality and physical activity [30]. To illustrate, food insecurity might influence weight through changing physical activity and therefore physical activity is considered a potential mediator.…”
Section: Potential Mediating Variables and Covariatesmentioning
confidence: 99%
“…The impact food insecurity has on college students is also a concern. Studies have shown that college food insecurity is associated with inadequate diet quality [8][9][10][11] along with poor health outcomes, including self-rated health [8,[12][13][14][15][16][17][18], mental health, and weight status. Furthermore, food insecurity impacts academic performance, which is counterintuitive to the obtainment of a college degree [8,12,15,16,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%